Technocare: Challenges in the post-covid era - Martín Palomo, María Teresa; Gómez Bueno, Carmuca; González Calo, Inés (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
The relationship between care and technoscience generates a highly dynamic field of study in the social sciences, such as the project in which the results presented here have been incorporated (anonymised). This article analyses the implications of technology on the specific work of the Home Help Service (HHS). To do so, a longitudinal qualitative approach was conducted through interviews with HHS auxiliaries whose discourses provide an opportunity to study how care practices have been reconfigured by technology following the onset of the pandemic. Other aims that have focused the analysis are to discover the requirements with regard to competencies, abilities and skills that the new situation requires to be mobilised as well as the demands that this entails; and to identify how they help to define care with technologies in a space that tends to resist changes such as the domestic environment.